Canarias Dak'Art 2004. - Jinorio, Orlando Britto; Hernández, Celestino; Muñoz, Clara; Zaya, Antonio; Dakar ([S.l.] : [s.n.], 2004)
Arozena, Teresa ; Gonzalez, Gregorio ; Ruiz, José ; Torrens, Nestor ; Batista, Juan Carlos ; Galarza, Elena ; Gonzalez, Gonzalo ; Hernandez, Pipo ; Palmero, Luis ; Ruiz, José Maria ; et al.
Dakar, 2004
kunstcatalogus